Developing the Elementary Schools' Healthy Living Culture Teaching Materials Based on the Local Wisdom - Rury Rizhardi; Ali Fakhrudin; Aldora Pratama (Universitas PGRI Palembang, 2022)
This study shapes to produce teaching materials for a healthy life culture in elementary schools based on the local wisdom. The method used in this study was a research and development method with the research subject being the first grade students of SD Negeri 184 Palembang, totaling 32 students. This study followed the development of the ADDIE model with five stages, namely Analysis, Design, Development, Implementation, and Evaluation. Data collection techniques used expert validation sheets, student response questionnaires, and achievement tests. From the validation results obtained an average assessment of 88.45% with a very valid category. In the big group test stage, the average result was 89.5% thus it could be stated as very practical. Based on the results of the study, it was found that the teaching materials for healthy living culture in Elementary Schools with local wisdom were already considered as valid and practical teaching materials.